Cytokine profile in children with food allergy following liver transplantation. (20th January 2020) - Haflidadottir, Svanhildur; Matthews, Iren Lindbak; Almaas, Runar
Abstract: Background: LTX in children is associated with increased risk of food allergy, and the mechanisms underlying this are unknown. We wanted to study whether plasma cytokine profile differed in liver transplanted children, with and without food allergy, and whether it differed from untransplanted children with CLD. Methods: Plasma cytokines, total and specific IgE in nine patients with food allergy were compared with 13 patients without food allergy following LTX, and also with seven untransplanted patients with CLD. Results: No difference was found in the cytokine profile between liver transplanted patients with and without food allergy. Transplanted patients with food allergy having received a prescription of epinephrine had a significantly higher total IgE (2033 [234‐2831] vs 10 [5‐41] IU/L, P = .002) and MIP‐1b (52 [37‐96] vs 36 [32‐39], P = .035) compared with transplanted patients without food allergy. Two patients with severe food allergy responded favorably to conversion from tacrolimus‐based immunosuppression to MMF and corticosteroids with reduction in clinical symptoms, total IgE, specific IgE, IL‐1ra, IL‐4, RANTES, PDGF, MIP‐1a, and TNFα. The transplantation group had higher levels of IL‐1b, IL‐5, IL‐7, IL‐13, GCSF, IFNγ, and MIP‐1a compared with the CLD group. Conclusions: No overall difference was found in plasma cytokine profile between patients with and without food allergy. Patients with severe food allergy had significant elevation of MIP‐1b. Discontinuation of tacrolimus reduced total and specific IgE and changed plasma cytokine profile. The plasma cytokine profile in liver transplanted children was different compared with children with CLD.